PERFORMANCE OF THE MULTIDISCIPLINARY TEAM REGARDING THE APPROACH TO PALLIATIVE CARE IN NEUROLOGICAL PATIENTS (Cadernos ESP, 2025)
Objective: describe the performance of the multidisciplinary team regarding the approach to palliative care in neurological patients. Methods: descriptive, cross-sectional and quantitative study, carried out from February to April 2024 with the multidisciplinary team of a unit at the General Hospital of Fortaleza. An electronic form was used, with sociodemographic data, six objective questions and one open question about palliative care. Results: 18 professionals participated, 83% were women, 88% were between 25 and 44 years old and 38.8% had 6 to 10 years of experience. Regarding palliative care, 88.9% stated that it promotes the quality of life of patients and families, who face life-threatening illnesses, through the prevention and relief of physical, psychosocial and spiritual suffering; 66.7% stated that they were initiated upon severe diagnosis; 94.4% agreed that it promotes the quality of life of the patient and family through the prevention and relief of suffering; 77.8% stated that care covers the patient, family and caregiver; 77.8% indicated care in hospitals, homes and outpatient clinics; 55.6% believe that invasive measures should not be carried out in patients with therapeutic limitations and in an active process of death. Relief from pain/suffering was the most cited finding in the open question. Conclusion: The team still has a limited understanding of palliative care, highlighting the need to expand knowledge on the topic, especially in relation to neurological patients. Considering that most neurological diseases have no cure and compromise quality of life, it is essential to strengthen this approach. Therefore, the study adds to the literature by expanding this understanding of the application of palliative care in this patient profile.
Keywords: Multidisciplinary team; Neurological disorders; Palliative care